AKUNTANSI PENERIMAAN KAS DAN PENGELOLAAN KAS PADA PT. BANK RIAU KEPRI CABANG PEMBANTU KOTA TENGAH - Yuliza, Arma (E-Journal Cano Ekonomos, 2013)
Cash represent most fluent asset in meaning often change because most company transaction relate to cash. Accountancy cash inflow and management of cash represent one of the activity of routine an company. This research is executed by at PT. bank of Riau ministrant Branch kepri of Middle Town. This Research use descriptive method that is data obtained is hereinafter compiled by aspect and of pursuant to relevant theory with problems. From result of research which have can know that especial source of obtained cash inflow come from society deposit and prima facie management is gift of credit, especially to assist middle economic society under. Pursuant to research which is writer do at PT. Bank of Riau Ministrant Kepri Branch of Middle Town indicate that acceptance and management of cash have walked better, fluent and effective. But still there are some other comparison which caused by the lack of accuracy in making of budget so that happened difference which far.